2018 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2018
DOI: 10.1109/icsme.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation of Test Smells to Software Code Quality

Abstract: Test smells are sub-optimal design choices in the implementation of test code. As reported by recent studies, their presence might not only negatively affect the comprehension of test suites but can also lead to test cases being less effective in finding bugs in production code. Although significant steps toward understanding test smells, there is still a notable absence of studies assessing their association with software quality.In this paper, we investigate the relationship between the presence of test smel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 76 publications
5
111
2
4
Order By: Relevance
“…Among all these studies, Khomh et al [52] showed that the presence of sub-optimal implementations in Java classes, i.e., code smells, has a strong impact on the likelihood that such classes will be often modified by developers. The results were later confirmed by several studies in the field [22,75,83,107], further highlighting the relevance of code smells for change-proneness. Our work is clearly based on these findings, and aims at providing additional evidence of how code smells can be adopted in the context of prediction models having the goal of identifying change-prone classes.…”
Section: Related Worksupporting
confidence: 64%
“…Among all these studies, Khomh et al [52] showed that the presence of sub-optimal implementations in Java classes, i.e., code smells, has a strong impact on the likelihood that such classes will be often modified by developers. The results were later confirmed by several studies in the field [22,75,83,107], further highlighting the relevance of code smells for change-proneness. Our work is clearly based on these findings, and aims at providing additional evidence of how code smells can be adopted in the context of prediction models having the goal of identifying change-prone classes.…”
Section: Related Worksupporting
confidence: 64%
“…Our participants revealed that finding how to design a test code to avoid flakiness is an important challenge to face. This motivates the growing research area around test code quality [18,29,[33][34][35][36][37] and provides two promising directions that the research community can focus on: (i) the definition of a set of design patterns that can support the creation of deterministic tests; (ii) the definition of a set of flakiness-related anti-patterns that practitioners should avoid when writing test cases. While some initial steps have been done about the relation between test smells and flaky tests [31,32], further investigation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Test smells represent sub-optimal design or implementation choices applied by developers when defining test cases [15], [33], [34]. On the one hand, previous research showed that the presence of test smells can lead the test code to be less maintainable [35]- [37]. On the other hand, recent work demonstrated that test smells can be related to problems like test flakiness or fault-proneness of test and production code [37], [38].…”
Section: Test Smellsmentioning
confidence: 99%
“…On the one hand, previous research showed that the presence of test smells can lead the test code to be less maintainable [35]- [37]. On the other hand, recent work demonstrated that test smells can be related to problems like test flakiness or fault-proneness of test and production code [37], [38]. Thus, test smells may negatively influence the overall ability of a test case to find faults in production code.…”
Section: Test Smellsmentioning
confidence: 99%
See 1 more Smart Citation